Invitation to the International Secretariat for the Natural Sciences of the World Black Researchers Association - World Black Researchers Association (1977)
Invitation to the founding congress of the International Secretariat for the Natural Sciences of the World Black Researchers Association. Anthropologist and physicist Cheikh Anta Diop (1923-1986) wrote the invitation, on behalf of the World Black Researchers Association (WBRA).
Keywords: Diop, Cheikh Anta; World Black Researchers Association; African American scientists